Minor Change of Plasma Renin Activity during the Saline Infusion Test Provide an Auxiliary Diagnostic Value for Primary Aldosteronism. (17th February 2021) - Adilijiang, Munire; Luo, Qin; Wang, Menghui; Zhang, Delian; Yao, Xiaoguang; Wang, Guoliang; Zhou, Keming; Li, Nanfang
Abstract : Context . Failure of plasma aldosterone suppression during the saline infusion test (SIT) confirms primary aldosteronism (PA); recommendations for diagnostic strategies are currently controversial in the case of an inconclusive test result with a post-SIT PAC 5–10 ng/dl, while the renin change during SIT is not focused by the previous study. Objective . To clarify whether it has some hidden diagnostic values for PA, especially in the case of an inconclusive SIT result, we investigated the difference in changes of plasma renin activity (PRA) during SIT between patients with PA and non-PA. Methods . We measured and compared the SIT parameters of 159 PA patients, 368 non-PA patients, and 43 inconclusive patients who were included in this study. Results . The PA group showed a minor change of PRA during the SIT (ΔPRA, defined as (pre-SIT PRA–post-SIT PRA)) compared with the non-PA group (0.17 ng/ml/h vs. 1.07 ng/ml/h, P < 0.001 ). According to ROC analysis, ΔPRA showed a greater AUC than post-SIT PRA (0.897 vs. 0.855, P < 0.001 ). The cutoff value was 0.5 ng/ml/h, with 90.3% sensitivity and 78.6% specificity. When combined with ARR post-SIT, it showed 81.6% sensitivity and 97.0% specificity for PA diagnosis. Further analysis of 43 patients with an inconclusive SIT result who completed AVS found that ΔPRA was smaller in the confirmed PA group compared with the unconfirmed PA group (0.19 ng/ml/h vs. 0.29 ng/ml/h, P < 0.05 ); there was no significant difference in PAC post-SIT between two groups. ΔPRA ≤ 0.21 ng/ml/h provides 71.4% sensitivity, 80.0% specificity, and 87.0% PPV for their PA diagnosis. Conclusions . PA patients show minor PRA change during SIT; the change of PRA during SIT provides an auxiliary diagnostic value for PA, especially in patients with an inconclusive SIT result.